PENGARUH FAKTOR PERSONAL TERHADAP KOMITMEN ORGANISASIONAL GURU MADRASAH - Akbar, Rofiq Faudy (QUALITY, 2019)
This study aims to examine the influence of personal factors on organizational commitment. Personal factors in this study are interpreted with job choice factor, expectancy, and psychological contract variables. Research respondents were private madrasa teachers in the Central Java Indonesia. Data analysis using structural equation modeling partial least square shows that personal factors have a positive and significant effect on teacher organizational commitment. Job choice factor is the consideration of the applicant the first time someone decides to work as a teacher. Individuals have evaluated salary, the nature of the type of work as an educator, as well as long-term prospects such as the possibility to become permanent teachers of a madrasa / school and the opportunity to get certified. Teachers have expectations regarding financial and non-financial compensation and hope the head of the madrasa or foundation provides reciprocity or appreciation for their sacrifice to the organization. Teachers always expect a positive response from the  head of the madrasa/foundation, as their workload increases. Positive responses from the head of the madrasa/foundation provided their commitment to work and organization will always increase, conversely.